Cultural mega-events : opportunities and risks for heritage cities - Jones, Zachary M. (Abingdon, Oxon ; New York : Routledge, 2020)
"Mega-events have long been used by cities as a strategy to secure global recognition and attract future economic investment. While cultural mega-events have become increasingly popular, cities have begun questioning the traditional model of other events such as the Olympic Games with many candidate cities cancelling bids in recent years. This book explores how to resolve this issue, to reduce overall costs and increase sustainability, by further embedding events within the existing fabric of the city. Cultural mega-events have been employing this strategy for several decades, resulting in a broad range of physical effects and nuanced institutional changes. Cultural Mega-Events highlights this growing trend and positions them within a broader discussion of mega-events, through an examination of three World Heritage cities, Genoa, Liverpool and Istanbul that have hosted the European Capital of Culture. By doing so, it investigates the benefits and challenges of integrating event and heritage planning to provide lessons that can help future historic cities"--
Introduction: Mega-events and the city -- The rise of cultural mega-events and shifting mega-event trends -- Defining cultural mega-events and the mega-event process -- The potential synergy between built heritage and mega-events -- Genoa European Capital of Culture 2004: A cultural mega-event embedded within a strategic vision for heritage development -- Istanbul European Capital of Culture 2010: Competing visions for heritage in a cultural mega-event -- Key issues emerging from the overlap of heritage and mega-events -- Conclusions: Considerations for future historic cities hosting mega-events.
OCLC-licensed vendor bibliographic record.
Keywords: European Capitals of Culture (Initiative); Hosting of sporting events -- Economic aspects; Hosting of sporting events -- Social aspects; ARCHITECTURE / Landscape; ARCHITECTURE / Urban & Land Use Planning